(untitled) (Malaysian Journal of Civil Engineering, 2018)
With a predicted rapid international and regional trade within the region, the Northern road transport corridor will have to deal with the challenges associated with additional traffic growth without compromising on travel time, safety and environmental concerns. Towards this, the Kenyan government embarked on the construction of the Standard Gauge Railway Line (SGRL) in order to improve the Northern Corridor network performance so as to enhance the logistics competitiveness along the corridor. The paper presents the findings of an ongoing research into the impacts of freight traffic on roadway capacity related elements such as travel time, speed, volume to capacity ratios as well as ozone emissions on the corridor. Under the plausible economic growth regime, the SGRL will only divert a maximum of 20% of freight demand from the road network and is expected to reduce capacity on the network, reduce travel time, minimize emissions concentrations and improve the entire network reliability. However, this will depend on the rail modal split capacity, and as such the excess capacity will only be handled by the road network which in turn will result into capacity constraints beyond the 2025. Further, the SGRL will result in substantial reduction of Ozone concentration along the network up to the forecast year 2020 only, beyond which the Ozone concentration on some sections of the corridor will begin to exceed the acceptable WHO standards of 100Î¼g/m3.